Comparison of relative age of elite athletes participating in the 2008 Brazilian soccer championship series A and B - Costa, V. T.; Simim, M. A.; Noce, F.; Costa, I. T.; Samulski, D. M.; Moraes, L. C. (Performance Enhanced By Bridging The Gap Between The Theory And Practice, 2009)
In relation to the semester of birth, our results confirm the results of Vaeyens et aI. (2005), who also found a prelerence lor 1St semester-born athletes in a longitudinal study 01 Belgian soccer athletes. Musch and Hay (1999) compared the relative age plots lor the general population of different countries (Brazil, Japan, Australia, and Germany) and for professional soccer players and identified a significant preference for 1St semester-born players. The analysis 01 the differences lound in birth date quartile reveals that they are very close to the results in the international literature. Glamser and Vicent (1999) investigated birth date quartile in American athletes and concluded that athletes born in the beginning of the year who became professionals predominate. Musch and Hay (1999) also found the predominance 01 soccer players born in the 1St and 2nd quartiles in a study 01 professional athletes from different social-cultural contexts and countries when compared to the general population. A decade later, the results found in the Brazilian professional soccer for year 2008 are s imilar to those reported by Musch and Hay (2999) in their analysis of Brazílian championship professionals (2995-2996) with the clubs' preference for athletes born in the 2St and 2nd quartíles over 50% of the sample and a low score of athletes born in the 4th quartile. Therefore, we concludee that the relative age stands out as a variable in the elite soccer athlete selection and training, as the comparisons show the clubs ' preference for athletes born early in the year. However, it is necessary to analyze the relative age phenomenon in Brazilian soccer from a broader perspective considering aspects like sports organization in Brazilian athlete training, biological and maturational parameters, and socio-cultural aspects. In fact, a type of research we are conducting now .